A STRUCTURAL SEMANTIC FEATURES IN TRANSLATION OF AVIATION TERMS: STRUCTURAL SEMANTIC FEATURES IN TRANSLATION OF AVIATION TERMS - Xadjayeva, Mahliyo (Журнал иностранных языков и лингвистики, 2022)
The article discusses the wide spread problems, semantic structural features of translation in field of aviation. Additionally, there contained word formation which are common in this branch of technology and popular word formations as well. By means of investigation the terms it is seen obvious that the significant features are performed in the form of abbreviations. Therefore, the article focuses on structural features and semantic peculiarities of abbreviation in aviation. Majority of the provided sample terms are as abbreviations, clippings and acronyms.